Advances in Carbon–Element Bond Construction under Chan–Lam Cross-Coupling Conditions: A Second Decade - Vijayan, Ajesh; Rao, Desaboini Nageswara; Radhakrishnan, K. V.; Lam, Patrick Y. S.; Das, Parthasarathi (Synthesis, 2020)
Copper-mediated carbon–heteroatom bond-forming reactions involving a wide range of substrates have been in the spotlight for many organic chemists. This review highlights developments between 2010 and 2019 in both stoichiometric and catalytic copper-mediated reactions, and also examples of nickel-mediated reactions, under modified Chan–Lam cross-coupling conditions using various nucleophiles; examples include chemo- and regioselective N-arylations or O-arylations. The utilization of various nucleophiles as coupling partners together with reaction optimization (including the choice of copper source, ligands, base, and other additives), limitations, scope, and mechanisms are examined; these have benefitted the development of efficient and milder methods. The synthesis of medicinally valuable or pharmaceutically important nitrogen heterocycles, including isotope-labeled compounds, is also included. Chan–Lam coupling reaction can now form twelve different C–element bonds, making it one of the most diverse and mild reactions known in organic chemistry.1 Introduction2 Construction of C–N and C–O Bonds2.1 C–N Bond Formation2.1.1 Original Discovery via Stoichiometric Copper-Mediated C–N Bond Formation2.1.2 Copper-Catalyzed C–N Bond Formation2.1.3 Coupling with Azides, Sulfoximines, and Sulfonediimines as Nitrogen Nucleophiles2.1.4 Coupling with N,N-Dialkylhydroxylamines2.1.5 Enolate Coupling with sp3-Carbon Nucleophiles2.1.6 Nickel-Catalyzed Chan–Lam Coupling2.1.7 Coupling with Amino Acids2.1.8 Coupling with Alkylboron Reagents2.1.9 Coupling with Electron-Deficient Heteroarylamines2.1.10 Selective C–N Bond Formation for the Synthesis of Heterocycle-Containing Compounds2.1.11 Using Sulfonato-imino Copper(II) Complexes2.2 C–O Bond Formation2.2.1 Coupling with (Hetero)arylboron Reagents2.2.2 Coupling with Alkyl- and Alkenylboron Reagents3 C–Element (Element = S, P, C, F, Cl, Br, I, Se, Te, At) Bond Forma tion under Modified Chan–Lam Conditions4 Conclusions
Keywords: Chan–Lam coupling; C–O bond formation; C–N bond formation; N-arylation; copper-catalyzed; copper mediated